2000
DOI: 10.1007/s10434-000-0305-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Immunohistochemically Localized Biomarkers in Stage II and Stage III Breast Cancer: A Multivariate Analysis

Abstract: p53 expression in primary tumors was an independent prognostic factor that influenced relapse-free survival in patients with stage II disease. In stage III patients, lack of Bcl-2 expression was independently associated with a poor prognosis and, thus, may be an indicator of aggressive phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
21
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 23 publications
9
21
4
Order By: Relevance
“…The percentage positivity of p53 immunohistochemistry of the present study is almost similar to the reported statistics of most of the studies [14,20,[22][23][24][25][26] except, it is high in studies done by Bhatavdekar et al, [25] and Silvestrini et al, [26]. In maximum number of studies the average percentage of p53 positivity in breast cancers ranges from 18% to 36% [13].…”
Section: Discussionsupporting
confidence: 88%
“…The percentage positivity of p53 immunohistochemistry of the present study is almost similar to the reported statistics of most of the studies [14,20,[22][23][24][25][26] except, it is high in studies done by Bhatavdekar et al, [25] and Silvestrini et al, [26]. In maximum number of studies the average percentage of p53 positivity in breast cancers ranges from 18% to 36% [13].…”
Section: Discussionsupporting
confidence: 88%
“…In this regard, our results are in contrast with studies that suggest that bcl-2 expression is a favourable prognostic factor when primary surgical therapy is used. In other studies bcl-2 expression has been found to be an independent predictor of prognosis (7,8,12,10,18,38). However, other studies have shown opposite results (6,25,35,36,47).…”
Section: Discussionmentioning
confidence: 77%
“…Alterations in the proto-oncogene HER-2/neu have been extensively studied in Western and east Asian females with breast cancer and proposed as prognostic markers of potential clinical utility [11][12][13][14][15][16][17]. However, few studies exist on prognostic signifi cance of these oncogenes in female breast cancer in developing countries particularly in India [18].…”
Section: Introductionmentioning
confidence: 99%